Los abordajes conceptuales a la migración de retorno: una revisión sistemática de los marcos teóricos (1974-2018) y sus implicancias para el caso peruano - Corzo Vargas, Stefano Sebastian (2024)
This article offers an overview of the main theoretical approaches to return migration developed over the past five decades: Bovenkerk (1974), Gmelch (1980), King (2000), Cassarino (2004), Durand (2004), and Batistella (2018). Before exploring the typologies proposed by each author, the article critically examines the multiple definitions of return as a specific moment of the migratory path and highlights key trends in case studies of specific returns over the same chronological period. The article analyzes different conceptual typologies of return, outlining their major contributions and limitations. It concludes by offering insights for understanding contemporary return for the Peruvian case in particular.